2022
DOI: 10.3390/medicina58121791
|View full text |Cite
|
Sign up to set email alerts
|

Suboccipital Muscles, Forward Head Posture, and Cervicogenic Dizziness

Abstract: Dizziness or vertigo can be caused by dysfunction of the vestibular or non-vestibular systems. The diagnosis, treatment, and mechanism of dizziness or vertigo caused by vestibular dysfunction have been described in detail. However, dizziness by the non-vestibular system, especially cervicogenic dizziness, is not well known. This paper explained the cervicogenic dizziness caused by abnormal sensory input with references to several studies. Among head and neck muscles, suboccipital muscles act as stabilizers and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 100 publications
0
12
0
Order By: Relevance
“…[28] Suboccipital muscles are known to be associated with maintaining body posture as well as head rotation. [29,30] The suboccipital muscles spindles have high-density large diameter fibers that transmit proprioceptive information. [30,31] Suboccipital muscle inhibition technique was used to relax tension in the suboccipital muscles, which help to regulate the proprioceptive information.…”
Section: Interpretation Of the Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[28] Suboccipital muscles are known to be associated with maintaining body posture as well as head rotation. [29,30] The suboccipital muscles spindles have high-density large diameter fibers that transmit proprioceptive information. [30,31] Suboccipital muscle inhibition technique was used to relax tension in the suboccipital muscles, which help to regulate the proprioceptive information.…”
Section: Interpretation Of the Resultsmentioning
confidence: 99%
“…[29,30] The suboccipital muscles spindles have high-density large diameter fibers that transmit proprioceptive information. [30,31] Suboccipital muscle inhibition technique was used to relax tension in the suboccipital muscles, which help to regulate the proprioceptive information. These fibers transmit proprioceptive signals that effectively inhibit damage perception signals from reaching the spinal cord and higher centers.…”
Section: Interpretation Of the Resultsmentioning
confidence: 99%
“…Neck pain occurs due to a process of chemical stimulation in the form of arachidonic acid release by muscle cells that experience spasm, irritation and result in local ischemia, triggering the production of prostaglandins, thromboxanes, monohydroxy fatty acids, and leukotrienes that trigger the release of active pain complements such as serotonin, histamine and bradykinin. 11 Ultrasound provides a mechanical effect in the presence of the resulting pressure that can stimulate C afferent nerve fibers, resulting in dilation of capillary blood vessels and hyperemia to help heal tissues. 12 In the tissues will increase the matrix; thus the matrix protein will increase so that its elasticity will increase and overcome the weakness of the flexor muscles and instability of the posterior longitudinal ligament in the forward head posture.…”
Section: Discussionmentioning
confidence: 99%
“…The cervical spine plays role in determining the position of the head on the trunk along with the visual and the vestibular systems [ 94 96 ]. Cervical zygapophyseal joints, especially from C1 to C3, and cervical muscles are widely provided with proprioceptors and mechanoreceptors, anatomically supporting that role [ 97 ]. Evidence from animal studies demonstrated the existence of close connections between vestibular nuclei and cervical proprioceptors potentially explaining eye, head, and neck coordination, perception of balance, and postural adjustments [ 9 ].…”
Section: Post Traumatic Craniocervical Disorders Reviewed From a Post...mentioning
confidence: 99%